ANALISIS SKILL CALON GURU BIOLOGI DALAM PENYUSUNAN LESSON PLAN SISTEM GERAK - Ramli, Murni; Nurmiyati, Nurmiyati; Ariyanto, Joko; Sapartiwi, Sapartiwi; Sukamti, Sukamti (EDUSAINS, 2017)
Abstract Human skeletal system is one of the important topics of grade XI of biology high school in Indonesia. This topic is commonly delivered by teacher in traditional method by following the order of the subtopics as written in the biology textbook. This research was a case study aimed to analyse the skills of trainee students on developing the lesson plan of skeletal system, which will be implemented during the field teaching practicum during the intership program. Two trainee students who were in the 7th semester are the participants of this research. Both were in the teaching practicum program in different schools. The skills of developing the lesson plan were analyzed by document analysis, observation of the practices, and measuring the satisfaction level of participant high school students who attended the classes. Both trainees had been guided by lecturers to construct inquiry, contextual and scientific approach-based lesson plan of skeletal system. The lesson plans made by student A and B are different, on indicators and intended learning, organizing the topics, approach and strategy of teaching, student activities, tools used, and the assessment. Lesson plan B is relatively close to inquiry-based activities and contextual teaching and learning. And according to students' satisfaction, lesson plan made by trainee B was more satisfied. The result may suggest that there should be a guidance, which can close the skills gap between trainee with different academic achievement Keywords: paedagogic skills; teacher training; lesson plan; skeletal system; high school biology Abstrak Sistem Gerak adalah salah satu topik penting di kelas XI SMA di Indonesia. Materi ini pada umumnya disampaikan oleh guru secara tradisional dengan cara mengikuti urut-urutan topik pada buku pelajaran biologi. Riset ini adalah studi perbandingan bertujuan untuk mempelajari bagaimana keterampilan dua mahasiswa calon guru dalam menyusun lesson plan sistem gerak yang dipraktekkan dalam Praktik Pengalaman Lapangan (PPL). Kedua mahasiswa adalah mahasiswa semester 7. Keterampilan dan kemampuan mahasiswa dianalisis melalui analisis dokumen lesson plan, observasi keterlaksanaan sintaks pembelajaran, serta tingkat kepuasan pada pembelajaran dari para siswa SMA peserta pembelajaran. Kedua mahasiswa diarahkan agar menggunakan pendekatan saintifik, kontekstual dan pembelajaran berbasis inkuiri. Lesson plan yang disusun mahasiswa (Lesson Plan A dan B) menunjukkan perbedaan pada penguraian kompetensi dasar menjadi indikator pembelajaran, strukturisasi materi, pendekatan dan strategi pembelajaran, aktivitas siswa, media yang dipergunakan, dan bentuk asesmen yang dipergunakan untuk menilai kompetensi siswa. Tingkat kepuasan siswa terhadap pengajaran kedua mahasiswa (Pembelajaran A dan B) juga dinilai berdasarkan penggunaan waktu, media, cara mengajar, kesempatan tanya jawab, diskusi kelas, dan presentasi. Siswa menunjukkan tingkat kepuasan yang lebih tinggi pada pembelajaran dengan Lesson Plan B. Munculnya perbedaan kemampuan menyusun lesson plan sistem gerak menunjukkan perlunya sistem pembimbingan yang dapat mengatasi gap capaian akademik dan kemampuan antarmahasiswa. Kata Kunci: skill pedagogik; training guru; desain pembelajaran; sistem gerak; biologi SMAÂ  Permalink/DOI: http://dx.doi.org/10.15408/es.v9i1.5476Â